PENANAMAN NILAI-NILAI PANCASILA SEBAGAI UPAYA PENINGKATAN KEDISIPLINAN ANGGOTA PASKIBRA SMK GANESHA TAMA BOYOLALI - karsono; Noviansyah, Wahyu (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
Pancasila stands as Indonesia's bedrock, encapsulating essential principles guiding national identity. The nation's trajectory hinges upon cultivating a disciplined, patriotically committed youth. Paskibra extracurricular activities emerge as pivotal in fostering both nationalism and the values intrinsic to Pancasila. This research analyzes the inculcation of Pancasila values as an effort to enhance the discipline of Paskibra members at SMK Ganesha Tama Boyolali. The findings reveal that the inculcation of Pancasila values through extracurricular Paskibra has proven effective in improving the discipline of Paskibra members in various aspects. Notable enhancements in punctuality, etiquette, and accountability have been observed among participants. The commendable efforts of SMK Ganesha Tama Boyolali in Pancasila education serve as a beacon for other educational institutions. By instilling Pancasila values early on, we can shape forthcoming generations into individuals characterized by discipline, responsibility, and unwavering integrity. Keywords: Extracurricular, Discipline, Pancasila, Paskibra.